2012
DOI: 10.5402/2012/935410
|View full text |Cite
|
Sign up to set email alerts
|

Eradication Treatment of Helicobacter pylori Infection: Its Importance and Possible Relationship in Preventing the Development of Gastric Cancer

Abstract: Helicobacter pyloriis the most important carcinogen for gastric adenocarcinoma. Bacterial virulence factors are essential players in modulating the immune response involved in the initiation of carcinogenesis in the stomach; host genetic factors contribute to the regulation of the inflammatory response and to the aggravation of mucosal damage. In terms of environmental factors, salt intake and smoking contribute to the development of lesions. Various therapeutic schemes are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 98 publications
(115 reference statements)
0
11
0
3
Order By: Relevance
“…[ 48 ] A separate review of the eradiation trials concluded that there is a point of no return with respect to the development of H. pylori associated gastric cancer after which time treatment is ineffective at reducing the risk of malignancy. [ 49 ] Until date, the true impact of eradication of the bacteria is unknown.…”
Section: Diffuse Subtypementioning
confidence: 99%
“…[ 48 ] A separate review of the eradiation trials concluded that there is a point of no return with respect to the development of H. pylori associated gastric cancer after which time treatment is ineffective at reducing the risk of malignancy. [ 49 ] Until date, the true impact of eradication of the bacteria is unknown.…”
Section: Diffuse Subtypementioning
confidence: 99%
“…Helicobacter pylori ( H. pylori ) was introduced to scientific society in the 1980s by Marshal and Warren, when they announced that the bacterium can be a cause for active chronic gastritis and peptic ulcer disease [ 1 ]. Since that time research was started on the subject and to date it has shown that the microorganism can cause several diseases involving the gastrointestinal tract, including acute and chronic gastritis, atrophic gastritis, peptic ulcer disease, gastric mucosa-associated lymphoid tissue (MALT) lymphoma, and gastric adenocarcinoma [ 2 ]. Among extraintestinal diseases, the bacillus has been correlated t\ura [ 3 ], unexplained iron-deficiency anaemia [ 4 , 5 ], and idiopathic thrombocytopenic purpura (ITP) [ 6 ], and its eradication has been recommended in these cases.…”
Section: Introductionmentioning
confidence: 99%
“…The recognition that Hp can cause GAC led WHO to consider Hp as a carcinogenic agent [24] and to promote its eradication as one of the strategies to prevent the disease, even after tumor resection [25,26].…”
Section: The Investigation Of Exogenous Elementsmentioning
confidence: 99%